Investigation of High-Risk ST131 Clone in Extended Spectrum β-Lactamase–Producing Escherichia coli Isolates in Children - Bulut, Mehmet E.; Hürkal, Gülen; Dalgıç, Nazan (Journal of Pediatric Infectious Diseases, 2021)
Objective Antimicrobial resistance poses a serious threat to children's health. In recent years, high-risk Escherichia coli ST131 has become an important target for global surveillance studies. The E.coli ST131 clone is associated with extended spectrum β-lactamase (ESBL) production, as well as multidrug resistance and treatment failure. Studies on this clone in the pediatric age group are limited. We aim to investigate the rate of high-risk E. coli ST131 clone in ESBL-positive E. coli isolates obtained from pediatric patients.Methods A total of 292 ESBL-positive E. coli isolates from clinical samples of pediatric patients was included in the study. MALDI-TOF MS system was used for bacterial identification. Susceptibility tests were performed using BD Phoenix automated system. ST131 detection was done by MALDI-TOF-MS. Fisher's exact test was used to compare the groups (significance <0.05).Results A total of 292 isolates was analyzed. The high-risk ST131 clone was detected in 117 (40%) of the 292 ESBL-positive isolates. ST131 rates were found to be significantly higher in children under the age of 5 years compared with children over the age of 5 years (49.3 vs. 31.1%, p = 0.0019). Ciprofloxacin resistance was higher in ST131 isolates (45.6 vs. 31.7%; p < 0.05).Conclusion The rate of the ST131 clone was found to be high in the pediatric population. The significantly high rate of resistance to ciprofloxacin, which is not commonly used in the pediatric population, in ST131 isolates reveals the importance of the spread of high-risk clones for the development of resistance.
Keywords: pediatric infection; Escherichia coli ST131; ESBL; high-risk clone